Neolithic and industrial revolutions - Macfarlane, Alan (Apollo - University of Cambridge Repository, 2004)
Looking out over the city of Kathmandu, Alan Macfarlane briefly summarizes two of the great revolutions in human history, the neolithic and industrial.